New Zealand Echinoderms - Fell, Howard Barraclough (The University of Edinburgh, 1955)
1. The Direct Development of a New Zealand Ophiuroid || 2. Echinoderms from the Subantarctic Islands of New Zealand: Asteroidea, Ophiuroidea, and Echinoidea || 3. The Constitution and Relations of the New Zealand Echinoderm Faun || 4. Echinoderms from Southern New Zealand || 5. A Revision of the Current Theory of Echinoderm Embryology || 6. Echinoderm Embryology and the Origin of Chordates || 7. New Zealand Fossil Asterozoa: 3. Odontaster priscus sp. nov. from the Jurassic || 8. An Echinoid from the Tertiary (janjukian) of South Australia Brochopleurus Australiae sp. nov. || 9. Probable Direct Development in Some New Zealand Ophiuroids || 10. The Origin and Migrations of Australasian Echinoderm Faunas Since the Mesozoic || 11. An Upper Cretaceous Asteroid from New Zealand || 12. A Giant Heart - Urchin || 13. A Triassic Echinoid from New Zealand || 14. Sonne Off' Shore and Deep-Sea Ophiuroids from New Zealand Waters || 15. The Occurrence of Australian Echinoids in New Zealand Waters || 16. Tertiary and Recent Echinoidea of New Zealand Cidaridae